Emergence of Endocytosis-Dependent mGlu1 LTD at Nucleus Accumbens Synapses After Withdrawal From Cocaine Self-Administration - Scheyer, Andrew F.; Christian, Daniel T.; Wolf, Marina E.; Tseng, Kuei Y. (Frontiers in Synaptic Neuroscience, 2018)
Extended-access cocaine self-administration induces a progressive intensification of cue-induced drug craving during withdrawal termed “incubation of cocaine craving”. Rats evaluated after >1 month of withdrawal (when incubation of craving is robust) display alterations in synapses onto medium spiny neurons (MSN) of the nucleus accumbens (NAc), including elevated levels of Ca2+-permeable AMPA receptors (CP-AMPAR) and a transition from group I metabotropic glutamate receptor (mGluR) mGlu5- to mGlu1-mediated synaptic depression. It is important to further characterize the emergent form of mGlu1-mediated synaptic depression because it has been demonstrated that mGlu1 stimulation, by normalizing CP-AMPAR transmission, reduces cue-induced cocaine craving. In the present study, we conducted whole-cell patch-clamp recordings in NAc core MSNs, comparing rats that underwent >35 days of withdrawal from cocaine self-administration to control rats that had self-administered saline. Bath application of the nonselective group I mGluR agonist dihydroxyphenylglycine (DHPG) produced a transient mGlu5-mediated synaptic depression in saline controls, whereas a persistent mGlu1-mediated synaptic depression emerged in cocaine rats. This form of long-term depression (LTD) was abolished by the inclusion of a dynamin inhibitory peptide in the recording electrode, indicating that it is mediated by removal of CP-AMPARs through a dynamin-dependent endocytosis mechanism. We further showed that CP-AMPAR endocytosis is normally coupled to the PICK1-mediated insertion of Ca2+-impermeable AMPARs (CI-AMPAR). Interestingly, this coupling is not obligatory, since the inclusion of pep2-EVKI in the recording electrode disrupted CI-AMPAR insertion, but spared mGlu1-mediated CP-AMPAR endocytosis. Collectively, these results reveal similarities but also differences from mGlu1-LTD observed in other brain regions, and further our understanding of a form of plasticity that may be targeted to reduce cue-induced craving for cocaine and methamphetamine.